Target America : a Sniper Elite novel - McEwen, Scott (Touchstone, a division of Simon & Schuster, Inc., 2014)
"From the coauthor of the bestseller American Sniper comes a heart-pounding military thriller in which the fabled domestic Special Ops Black unit is activated in order to stop a group of Chechen terrorists from launching a pair of "suitcase" nukes somewhere in America. When Chechen terrorists manage to smuggle a Cold War era Russian nuke across the Mexican-American border, the President is forced to reactivate the only unit capable of stopping them: Navy SEAL sniper Gil Shannon and his brash team of SEALs and Delta Force fighters. First introduced in Sniper Elite: One Way Trip, hailed by Publishers Weekly as a "meaty thriller" with "snappy dialogue and well-timed humor," Shannon and his team were run out of the military after defying direct orders and instead choosing to save the life of one of their own. In Target America, Gil and his team, many of whom had gone rogue, are reunited as an off-the-books Special Ops unit that must race against the clock to save the country from nuclear destruction."--